Dominant and non-dominant leg bone mineral density in professional soccer players and non-athlete subjects - Nazarian, A. B.; Khayambashi, K.; Rahnama, N. (World Journal of Sport Sciences, 2010)
The purpose of this study was to compare the bone mineral density (BMD) in dominant and non-dominant leg between professional soccer players and non-athlete subjects. Fifteen professional soccer players (mean±SD; age: 23.2±0.3 years, height: 174±1cm, weight: 70.3±1.8 kg) and fourteen healthy non-athlete subjects (mean±SD; age: 22 years, height: 173±1.2 cm, weight: 61.6±2.4 kg) participated in this study. All soccer players and control group were free of any illness such as diabetes, hyperthyroidism, hyperparathyroidism, cardiovascular disease and were not taking any medication. The participants did not report use of any antiseizure drugs, alcohol and cortoon consumption, neither smoking cigarette. The activity levels and dietary habits of all subjects were noted. BMD was measured by Dual Energy X-Ray Absorptiometry (DEXA) at the femoral neck and femoral trochanter of dominant and non-dominant legs. Paired sample and independent t-test were used to analyze the data. The results of this study showed that non-dominant leg of soccer players had significantly higher BMD than their dominant leg (T= 2.92, P= 0.01), (1335 versus 1288 mg/cm²). No significant difference was observed between dominant and non-dominant leg of control group (T= 0.05, P= 0.95), (941.1 versus 941.5 mg/cm²). The level of BMD of both legs of soccer players were significantly higher than control group (T=8.03, T= 8.58, P= 0.000), (1335 and 1288 mg/cm² versus 941.5 and 941.5 mg/cm²). Due to more frequent engagement of non-dominant leg in take off, landing and stance in shooting, BMD is higher than the other leg. Furthermore, it seems that soccer leads to increase of BMD in non-dominant and dominant leg in soccer players, which may be beneficial in the prevention of osteoporosis.